2014
DOI: 10.1111/jog.12384
|View full text |Cite
|
Sign up to set email alerts
|

Use of antidiabetic agents in the treatment of gestational diabetes mellitus in Germany, 2008–2012

Abstract: Aim: Adequate blood glucose control during pregnancy is important because gestational diabetes mellitus (GDM) is known to have adverse effects on the mother and child. Due to an increasing prevalence of GDM in recent years, more information on the use of different antidiabetic agents is required, which was the aim of the present study. Material and Methods: Data from 32 diabetic practices in Germany were collected from January 2008 to December 2012 and analyzed using the Disease Analyzer Database. All women wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
(64 reference statements)
3
6
0
Order By: Relevance
“…The pharmacological treatment rates in the present study were very similar to those reported in a German study that also looked at the distribution of glucose-lowering therapy use among women with GDM between 2008 and 2012 [15]. The authors of that study similarly observed significant increases over time in the proportion of women treated with any type of glucose-lowering therapy, the proportion who received metformin, and the proportion who were treated with insulin [15]. Sulfonylurea use was minimal in both studies, being used by only 0.07% of women with GDM in the present study and 0.2% in the German study.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The pharmacological treatment rates in the present study were very similar to those reported in a German study that also looked at the distribution of glucose-lowering therapy use among women with GDM between 2008 and 2012 [15]. The authors of that study similarly observed significant increases over time in the proportion of women treated with any type of glucose-lowering therapy, the proportion who received metformin, and the proportion who were treated with insulin [15]. Sulfonylurea use was minimal in both studies, being used by only 0.07% of women with GDM in the present study and 0.2% in the German study.…”
Section: Discussionsupporting
confidence: 86%
“…LGA rates were significantly higher in pregnancies receiving pharmacological treatment than in those that did not receive any pharmacological treatment, but did not differ significantly between those treated with insulin only or with metformin (+/-insulin). The pharmacological treatment rates in the present study were very similar to those reported in a German study that also looked at the distribution of glucose-lowering therapy use among women with GDM between 2008 and 2012 [15]. The authors of that study similarly observed significant increases over time in the proportion of women treated with any type of glucose-lowering therapy, the proportion who received metformin, and the proportion who were treated with insulin [15].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…11,12 In a large nationwide retrospective cohort study in the United States including 10,778 women with drug treated gestational diabetes, use of glibenclamide (glyburide) increased from 7.4% in 2000 to 64.5% in 2011, superseding insulin as most common treatment since 2007. 11 In spite of all these studies answer of the question which oral hypoglycaemic should be used for gestational diabetes?…”
Section: Introductionmentioning
confidence: 99%